The political significance of social ministries in Argentina, Chile and Uruguay - Midaglia, Carmen; Castillo, Marcelo; Fuentes, Guillermo (Estado, Gobierno y Gestión Pública, 2010)
Beginning in the 1990s, and as a result of the failure of market-oriented social-economic reforms, questions regarding poverty were reconsidered from a political perspective. At the same time, state institutions charged with overseeing new social policies and coordinating public policy directed at the poor were established: Social Development Ministries. This article studies these ministries institutional insertion, the mechanisms for relating with other state actors and their political orientation. The main findings point, on the one hand, towards the consolidation of ministerial control of the social protection sector while, on the other hand, demanding a series of responsibilities associated with the coordination of the social sphere. It would appear that current institutional structures are unprepared for this task.